Low Welfare Among Smallholder Palm Oil Farmers: Kesejahteraan yang Rendah di Kalangan Petani Kelapa Sawit Skala Kecil - Gilang Ramadan; Teguh Soedarto; Mirza Andrian Syah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The palm oil sector serves as a crucial pillar of the national economy and drives rural development. Specific Background Despite cultivating a high-value commodity, smallholder producers continuously face systemic financial pressures, including high operational expenses and unequal access to agricultural resources. Knowledge Gap Household-based prosperity measurement at the micro-level remains highly limited, necessitating a deeper empirical analysis to accurately depict real socioeconomic conditions. Aims This study investigates the financial status of local growers using the Farmer Household Income Exchange Rate approach and identifies the underlying structural determinants. Results Utilizing a snowball sampling method with seven key informants, the evaluation demonstrates an average exchange rate of 91.41, indicating that the majority of households have not achieved a prosperous condition. Furthermore, prosperity disparities are heavily dictated by land area, harvest yields, cost optimization, and alternative revenues. Specifically, fertilizer and labor expenses dominate the variable costs, suppressing net agricultural receipts. Novelty This research contextualizes the application of the Farmer Household Income Exchange Rate to reveal how simultaneous constraints in resource access and production expenses structurally prevent livelihood security. Implications Achieving continuous financial security requires comprehensive strategies prioritizing production cost optimization, alternative revenue diversification, and human resource capacity building rather than solely focusing on aggregate harvest volumes. Highlights: An average exchange rate of 91.41 signifies widespread financial vulnerability among local palm oil producers. Fertilizer and labor expenses heavily suppress net agricultural receipts within rural households. Revenue from non-farm sources successfully mitigates financial risks and ensures long-term livelihood security. Keywords: Palm Oil, Farmer Household Income Exchange Rate, Production Costs, Economic Sustainability, Smallholder Plantations